Implementasi pengajaran dan pembelajaran di rumah dalam norma baharu : persepsi guru - Hazura Mohamed; Kauthar Mohd Daud; Siti Fadzilah Mat Nor; Zaihosnita Hood (Penerbit Universiti Kebangsaan Malaysia, 2022)
A COVID-19 epidemic hit the country and saw a drastic shift to new norms, including education. Online teaching was previously only a teaching aid, but online teaching was already counted as the leading learning method during the pandemic. Teaching and learning at home (HTL) is a new norm educator must face. So, it is time for us to strengthen this online HTL to produce quality education. Thus, this study looks at the level of readiness of teachers to implement HTL using the Google Classroom platform efficiently. This study analyzes the level of readiness of teachers in terms of knowledge and skills to use Google Classroom in implementing HTL. In addition, the challenges of PdPR implementation are also studied in this study. A questionnaire survey method was used to achieve the objectives of the study. The study's findings show that teachers' knowledge and skills are still at a moderate level. The lack of student involvement during HTL is a major challenge teachers face. Improvements must be made to ensure that the issues mentioned can be addressed.